Differential ethylene sensitivity of epidermal cells is involved in the establishment of cell pattern in the Arabidopsis root. - Cao, X; Linstead, P; Berger, F; Kieber, J; Dolan, L (1999)
Root hairs of Arabidopsis roots develop on trichoblasts located over the anticlinal (radial) walls of underlying cortical cells. Non-hair cells, on the other hand, develop on atrichoblasts overlying the periclinal (tangential) walls of cortical cells. Dark-grown wild-type seedlings, which produce little ethylene, are largely root hairless. Exogenous treatment of dark-grown plants with either ethylene or 1-aminocyclopropane-1-carboxylic acid (ACC) restores the development of root hairs in cells overlying the anticlinal cortical cell walls, indicating that cells in this position are more sensitive to ethylene than atrichoblasts. We used mutations in genes that overproduce ethylene (eto1, eto2, eto3 and eto4) to illustrate the positive regulatory role of ethylene. The preferential development of root hairs on epidermal cells overlying the cortical anticlinal cell walls in these mutants also illustrates that trichoblasts are more sensitive to ethylene than atrichoblasts. CTR1 is a negative regulator of the ethylene response and might, therefore, be a candidate regulator of differential sensitivity. CTR1 mRNA is expressed in all cell types in the root, suggesting that its transcriptional pattern alone cannot account for the differential sensitivity of epidermal cells to ethylene. Cellular mapping of wild-type and mutant roots supports previous findings indicating that ethylene acts after, and perhaps independently, of TTG during the establishment of cell fate in the root epidermis.